2013
DOI: 10.1212/wnl.0b013e3182a08f2c
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and mechanisms of cortical superficial siderosis in cerebral amyloid angiopathy

Abstract: Objective: We investigated the prevalence and clinical-radiologic associations of cortical superficial siderosis (cSS) in patients with probable cerebral amyloid angiopathy (CAA) compared to those with intracerebral hemorrhage (ICH) not attributed to CAA. Methods:We conducted a retrospective multicenter cohort study of 120 patients with probable CAA and 2 comparison groups: 67 patients with either single lobar ICH or mixed (deep and lobar) hemorrhages; and 22 patients with strictly deep hemorrhages. We rated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
115
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(128 citation statements)
references
References 26 publications
10
115
0
1
Order By: Relevance
“…13 Another recent study found cSS in 40% of patients with a clinic-radiologic diagnosis of probable CAArelated ICH, but only 5% of patients with purely deep ICH, presumed to be due to hypertensive arteriopathy. 25 Increasing data support the hypothesis that cSS might precede lobar ICH in patients with CAA. 15,[26][27][28] In a recent retrospective study, 51 patients with cSS and no apparent cause other than CAA were identified through a single-center systematic database search and followed up for a median of 35.3 months.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…13 Another recent study found cSS in 40% of patients with a clinic-radiologic diagnosis of probable CAArelated ICH, but only 5% of patients with purely deep ICH, presumed to be due to hypertensive arteriopathy. 25 Increasing data support the hypothesis that cSS might precede lobar ICH in patients with CAA. 15,[26][27][28] In a recent retrospective study, 51 patients with cSS and no apparent cause other than CAA were identified through a single-center systematic database search and followed up for a median of 35.3 months.…”
Section: Resultsmentioning
confidence: 80%
“…29 The finding of cSS without previous ICH, and its tendency to occur distantly from previous ICH, favor this "primary" mechanism, 13,15 rather than leakage of blood into the subarachnoid space secondary to previous lobar "macro" ICH. 25 Consequently, cSS may be a marker of increased cortical and leptomeningeal small-vessel Figure 2 Time to symptomatic lobar ICH during follow-up…”
Section: Resultsmentioning
confidence: 99%
“…Larger studies could examine the influence of biomarkers of CAA 82,83 and other causes of ICH 84 on outcome and recurrent ICH. Because survivors of ICH have higher mortality in comparison with the general population 85 and given the apparently higher risk of ICH recurrence after lobar ICH ( Figure I in the online-only Data Supplement), 21 treatments directed at the specific small vessel diseases underlying ICH, such as CAA, may improve outcome (Study Evaluating the Safety, Tolerability and Efficacy of PF-04360365 in Adults With Probable Cerebral Amyloid Angiopathy, NCT01821118).…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence was higher than that in the general population (0.7%) but lower than in patients with cognitive impairment (6.1%) and patients with ICH because of probable CAA (≈40%). [19][20][21][22] CAA is proposed to be a cause of TFNE, which mimics the symptoms of TIA but is associated with high hemorrhage risk rather than the risk of recurrent ischemic stroke. Therefore, recognizing this syndrome is important to avoid escalating antithrombotic treatment in patients at a risk of hemorrhage.…”
Section: Discussionmentioning
confidence: 99%